Toward a Global Civilization of Love and Tolerance: By M. Fethullah Gülen (New Jersey: The Light, Inc., 2004. 269 pages.) (American Journal of Islam and Society, 2005)
This book presents the thoughts of M. Fethullah Gülen, one of the world’smost influential Muslim scholars today. His ideas are attractive to manypeople because they give guidance on how to combine Islamic values withcontemporary demands. Moreover, his emphasis on interfaith dialogue hasearned him an international audience from various religious backgrounds.Thus, Gülen’s movement has spread rapidly throughout the world withschools, cultural and media activities, and dialogue projects.This book is a compilation of Gülen’s writings, interviews, andspeeches that address such contemporary topics as interfaith dialogue, jihad,Sufism, and education. Moreover, it is among the first to address the timelyissue of dialogue among civilizations. The book clearly presents Gülen’sunderstanding of such a dialogue as a deliberate undertaking based uponlove, dialogue, and tolerance among people of different backgrounds.Readers who are not familiar with the context of these ideas in Turkish history,however, may find it difficult to follow the flow of some of his ideas.Gülen proposes dialogue for mutual enrichment and sharing as asolution to the “clash of civilizations” (p. 257), stating that the Abrahamicreligions, especially Islam, are against disorder, treachery, conflict, andoppression (p. 256). His model is based on people dedicating their livesto thought and activism for the sake of God and creation.Both Muslims and non-Muslims can benefit from this book. The authorreminds Muslims of Islam’s teachings on dialogue, using the Qur’an andthe Hadith to show that tolerance, love, and compassion have been the mainIslamic values throughout Islamic history and signify the importance of“reflecting God’s Mercy on themselves.” It may also help certain non-Muslims move beyond their prejudice, distrust, and misinformation andarrive at a deeper understanding of Islam. Gülen engages non-Muslims in ...